THE IMPACT OF BARCODE TECHNOLOGY ON CONSUMER BEHAVIOR IN PURCHASING FUEL: A STUDY OF EFFICIENCY AND EFFECTIVENESS - Edi Sumatirta; Irsyad Thalib Abdillah; Febri Ana (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study examines the impact of barcode technology implementation on consumer behavior in purchasing Pertalite fuel among subsidized vehicle owners in Serang City, Banten. Using a mixed-methods approach, data were collected through surveys and interviews with 120 fuel consumers receiving government subsidies and 10 gas station operators. The findings highlight the increased transaction efficiency and perceived effectiveness of barcode technology for Pertalite fuel purchases, although consumer trust and adoption levels vary based on age and digital literacy among subsidized consumers. These results provide insights into the digital transformation in energy retail services, particularly for subsidized fuel programs such as Pertalite.